New approaches to organocatalysis based on C–H and C–X bonding for electrophilic substrate activation - Nagorny, Pavel; Sun, Zhankui (Beilstein Journal of Organic Chemistry, 2016)
Hydrogen bond donor catalysis represents a rapidly growing subfield of organocatalysis. While traditional hydrogen bond donors containing N–H and O–H moieties have been effectively used for electrophile activation, activation based on other types of non-covalent interactions is less common. This mini review highlights recent progress in developing and exploring new organic catalysts for electrophile activation through the formation of C–H hydrogen bonds and C–X halogen bonds.
Keywords: C–H hydrogen bond; counteranion activation; electrophile activation; halogen bond donor; hydrogen bond donor; organocatalysis